Injury prevention in the developing world (Italian Journal of Public Health, 2010)
Injuries are rapidly escalating by-products of growth and urbanization in developing nations and have become the number one global health threat to children, young adults, and developing nations. Injuries are also highly preventable with scientifically evaluated, cost-effective solutions. Yet these same injuries are highly underappreciated as a global health threat and receive inadequate attention and funding. Because injuries so heavily affect individuals in their most productive years, their continued growth is sure to hamper or wipe away economic gains in many developing nations and further health inequities between developed and developing nations. Injury prevention in developing countries thus represents an enormous opportunity since attention and funding has been limited even in the face of evidence-based, cost-effective solutions. This opportunity should be pursued in developing nations by choosing prevention programs that address key injury threats and, at the same time, affect long-term, sustainable, and measurable injury reductions. Such programs should have strong local buy-in, a history of evaluation (preferably in developing nations), high returns-on-investment, make use of existing infrastructures when possible, and include an implementation plan that is to be carried out by the developing nation itself.
Keywords: Injury prevention; developing world